High-resolution residual terrain model and terrain corrections for gravity field modelling and geoid computation in Niger Republic - Ibrahim Yahaya, Salissou; El Azzab, Driss (Geodesy and Cartography, 2018)
In this study, we computed and presented grid maps of high-resolution terrain corrections and residual terrain model (RTM) as short-wavelengths of the gravity field and the geoid in Niger. We constructed RTM elevations from mean elevation surfaces corresponding to ~100 km and ~9 km of  spatial scales and 3 arc-seconds SRTM data. The computations are performed at gravity stations and 1.5 arc-minute regular grid, out to 10 and 200 km for inner and outer zones respectively with the standard density of 2670 kg/m-3. The study area is characterized by low values of terrain effects. The indirect effects are lower than 10 cm for ~9 km and reach 1.8 m for ~100 km. In Niger, 98.44% of indirect effects are lower than 1 cm and 98.2% of direct effect are lower than 5 mgal for ~9 km. For ~100 km, 85.87% of indirect effects are lower than 10 cm and 89.77% of direct effects are lower than 5 mgal for ~100 km, and 98.77% of terrain corrections are lower than 1 mgal. We found out that height discrepancies between gravity stations and SRTM influences the precision of terrain effects. The results are value for applications in geodesy and geophysics that require accurate interpretations.